The U.S. National Tips From Former Smokers Antismoking Campaign - Li‐Ling Huang; James F. Thrasher; Erika Nayeli Abad; K. Michael Cummings; Maansi Bansal‐Travers; Abraham Brown; Gera E. Nagelhout (2015)
Objective. Evaluate the second flight of the U.S. Tips From Former Smokers (Tips) campaign. Method. Data were analyzed from an online consumer panel of U.S. adult smokers before ( n = 1,404) and after ( n = 1,401) the 2013 Tips campaign launch. Generalized estimating equation models assessed whether the Tips advertisement recall was associated with knowledge about smoking-related risks in the Tips advertisements, awareness and use of a toll-free quitline and cessation websites, and quit attempts. Results. Seventy-one percent of participants at Wave 2 reported that they recalled seeing at least one Tips advertisement. Smokers who recalled seeing a Tips advertisement were more likely to (a) show increases over baseline in knowledge of health risks such as amputation: 65% versus 34%, p < .001; blindness: 27% versus 12%, p < .001; and (b) to be aware of a quitline (41% vs. 30%, p < .001) and cessation website (28% vs. 20%, p < .001). Recall of Tips advertisements was also associated with greater likelihood of reporting having visited cessation websites (odds ratio [OR] = 1.62, 95% confidence interval [CI] = 1.27-2.06), having called a quitline (OR = 2.28, 95% CI = 1.61-3.24), and having made a quit attempt (OR = 1.18, 95% CI = 1.00-1.39), although these results were only statistically significant in the unadjusted models. Conclusions. The 2013 Tips campaign was successful in increasing knowledge of health risks and awareness of tobacco cessation resources.